Redefining Excellence: AI-Enhanced Digital Competencies in Tertiary Education - Svoboda, Petr; Knihová, Ladislava (Publishing House of Wroclaw University of Economics and Business, 2024)
This chapter explores how AI and the demand for new competencies are reshaping university teaching, with a focus on instructional design, newskilling, and curriculum modernization. AI offers personalized learning experiences, fostering critical thinking and deeper engagement with educational materials. However, this transformation requires educators to adapt through newskilling and integrate ethical considerations into teaching. The findings indicate that AI has the potential to revolutionize higher education by equipping students with future-ready skills while simultaneously emphasizing the importance of preserving humanistic values such as empathy and interpersonal connections in teaching.
Svoboda, P. & Knihová, L. (2024). Redefining Excellence: AI-Enhanced Digital Competencies in Tertiary Education. In B. Drelich-Skulska, M. Sobocińska, A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 125-146). Publishing House of Wroclaw University of Economics and Business.
Keywords: AI-enhanced digital competency; educational technology; instructional design; newskilling; curriculum innovation